2010
DOI: 10.1021/ef100228b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of KOH/Coke Mass Ratio on Properties of Activated Carbons Made by Microwave-Assisted Activation for Electric Double-Layer Capacitors

Abstract: Activated carbons (ACs) are obtained by microwave-assisted activation of petroleum coke with KOH as an activation agent and used as electrode materials for electric double-layer capacitors. The pore structure and functional groups of ACs are characterized by Fourier transform infrared spectroscopy and the nitrogen adsorption technique. The results show that both the specific surface area (S BET) and the total pore volume (V t) of ACs go through a maximum as the KOH/coke mass ratio increases. At 5:1 of the KOH/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Carbon materials have been crucial for various fields of electrical energy storages such as capacitors, super capacitors, and secondary batteries with various electrodes [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbon materials have been crucial for various fields of electrical energy storages such as capacitors, super capacitors, and secondary batteries with various electrodes [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of the activated carbons obtained from biomass precursors have low bulk densities and physically weak structures, which are not appropriate for specific harsh purposes for example huge number of charge/discharge cyclic activities in EDLC and secondary battery electrodes [3]. Therefore, new carbon materials such as carbon nanotubes and graphene-based carbons have been synthesized as effective materials for these purposes [1][2][5][6][7][8][9][10][11]. Some recent super capacitors were made of a set of asymmetric electrodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been conducted to explore the electrochemical performance of activated carbon-based electrodes for EDLCs [10][11][12][13][14][15]. It has been reported that the capacitance of electrode critically depends on the pore structure and surface chemistry of activated carbon [16][17][18][19][20][21]. To improve its electrochemical performance, activated carbons must be modified with proper activation methods.…”
Section: Introductionmentioning
confidence: 99%
“…To improve its electrochemical performance, activated carbons must be modified with proper activation methods. The most extensively used methods is through one-step or two-step chemical and/or physical (thermal) activations using various modifiers such as ZnCl 2 , H 3 PO 4 , KOH, K 2 CO 3 , CO 2 , or steam [15,18,19,22,23]. However, such conventional processes are energy-intensive in conjunction with high temperature carbonization process (mostly conducted at above 700 1C) and often cause environmental issues due to the generation of wastewater containing toxic chemicals.…”
Section: Introductionmentioning
confidence: 99%